Chaperone Use in Plastic and Reconstructive Surgery Outpatient Clinics: The Patient Perspective. Issue 6 (December 2019) - Vakayil, Victor; Kim, Nicholas; Barta, Jo; Choudry, Umar
Abstract : Introduction: Patient perspectives on chaperone use during examinations, especially in surgical subspecialties, are understudied. We aimed to identify specific patient cohorts that desire the presence of chaperones and compare patient and surgeon perspectives, all in an effort to improve quality of care. Methods and Materials: We prospectively administered a 15-question survey to all patients visiting 2 plastic surgery outpatient clinics between January 2015 and April 2016. Data on demographics, types of procedures (cosmetic or reconstructive), area of examination (sensitive or nonsensitive), views on chaperone use, type of chaperone, and instances of inappropriate behavior by surgeons were collected. Univariate analysis was performed after stratifying patients on their individual desire to have a chaperone. Subsequently, multivariate regression models were constructed to identify individual patient cohorts independently more likely to require a chaperone. Results: A total of 398 participants were surveyed. There were 58.3% female and 41.7% male respondents; of whom 41.8% were 55 years or older and 8.1% were younger than 24 years. Ninety percent of all patients were receiving care for a reconstructive procedure. Most (77%) were being examined over a nonsensitive area. Overall, 82.1% preferred not to have a chaperone present during examinations. Most (72.6%) felt the sex of the examining physician was inconsequential to their need for a chaperone. Most (54.8%) preferred either a family member or a friend to be the chaperone. Only 1.8% (n = 7) experienced inappropriate behavior, of whom 77% (n = 5) noted the absence of a chaperone while being examined. On multivariate analysis, younger patients and examination over a sensitive area were independently associated with a higher odd of requiring a chaperone (odds ratios, 3.4 [95% confidence interval, 1.3–8.9; P = 0.016] and 3.9 [95% confidence interval, 1.9–6.7; P < 0.001], respectively). Conclusions: Most patients did not want a chaperone during examinations. Younger patients and those having a sensitive area examined were independently more likely to desire a chaperone. Patients preferred having their family member or friend as their chaperone. Given the major differences in perceptions, plastic surgeons should consider selectively using chaperones rather than the carte blanche use of chaperones with every patient. Abstract : Supplemental digital content is available in the text.